2017
DOI: 10.1112/jlms.12080
|View full text |Cite
|
Sign up to set email alerts
|

An application of a theorem of Emerton to mod p representations of GL 2

Abstract: Let p be a prime and L be a finite extension of Qp. We study the ordinary parts of GL2(L)representations arise in the mod p cohomology of Shimura curves attached to indefinite division algebras which splits at a finite place above p. The main tool of the proof is a theorem of Emerton.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Further, we compute it when G is split with connected centre (see Theorem 1.4 below). Note that in cases (ii) and (iii), the source of the isomorphism can be non-zero ( [Hu16]). Theorem 1.3 (Theorem 5.2.4).…”
Section: Presentation Of the Main Resultsmentioning
confidence: 99%
“…Further, we compute it when G is split with connected centre (see Theorem 1.4 below). Note that in cases (ii) and (iii), the source of the isomorphism can be non-zero ( [Hu16]). Theorem 1.3 (Theorem 5.2.4).…”
Section: Presentation Of the Main Resultsmentioning
confidence: 99%
“…Unlike the classical case of complex coefficients, this exact sequence does not necessarily split (cf. [Hu17]). We have the following necessary condition for the nonsplitting of the above exact sequence.…”
Section: 2mentioning
confidence: 99%
“…As an application of the above results, we study extensions of G-representations. Suppose we have a short exact sequence of the form 0 −→ Ind G B (χ) −→ π −→ τ −→ 0, where τ is an irreducible, admissible, supersingular representation of G. Hu has shown that such an extension does not necessarily split (contrary to the case of complex coefficients; see [Hu17]). Using the calculation of H 1 (I 1 , Ind G B (χ)), we give in Proposition 5.15 a necessary condition for the short exact sequence above to be nonsplit.…”
Section: Introductionmentioning
confidence: 99%
“…• Under the assumption of Buzzard-Diamond-Jarvis conjecture it was shown by Hu [Hu17] that for GL 2 (E) there are non-trivial extensions between supersingular and principal series representations which is not the case for GL 2 (Q p ) (we will come back to this point later in the introduction).…”
Section: Introductionmentioning
confidence: 99%
“…4.9] which states that the completed cohomology of Shimura curve (over a totally real field F ) realises the mod l local Langlands correspondences for GL 2 (F l ) where F l denotes the completion of F at the prime l (for the precise statement see Conjecture 1). The local factors appearing in Conjecture 1 is studied in [EH14], [Hel13] for primes l ∤ p and in [Hu17], [BHH + 20], [HW20] for primes lying above p. Therefore to salvage information about mod p local Langlands correspondence its natural to study the completed cohomology of Shimura curves. In fact in this article we will be also be concerned with the completed cohomology of ordinary and supersingular locus of Shimura curves.…”
Section: Introductionmentioning
confidence: 99%